Biomphalaria tenagophila: genetic variability within intermediate snail hosts susceptible and resistant to Schistosoma mansoni infection - Da Silva, D.; Spada, RGM; Sobral-Hamaguchi, S. S.; Abdel-Hamid, Z.; Zuim, NRB; Zanotti-Magalhaes, E. M.; Magalhaes, L. A.; Ribeiro-Paes, J. T. (Princeps Editions, 2004)
DNA analysis by molecular techniques has significantly expanded the perspectives of the study and understanding of genetic variability in molluscs that ere vectors of schistosomiasis. In tire present study, the genetic variability of susceptible and resistant B. tenagophila strains to S. mansoni infection was investigated using amplification of their genomic DNA by RAPD-PCR. The products were analyzed by PAGE and stained with silver. The results showed pdymorphism between tested strains with four different primers. We found two bonds of 1,900 and 3,420 bp that were characteristic of the susceptible strains with primer 2. The primers 9 end 10 identified a single polymorphic bond that was also characteristic of (3,136 and 5,041 bp, respectively) susceptible snails. Two polymorphic bonds were detected by primer 15: one with 1 800 bp was characteristic of the resistant strain and the other with 1,700 do in the susceptible one. These results provide additional evidence showing that the RAPD-PCR technique is adequate for the study of polymorphisms in intermediate hosts snails of S. mansoni. The obtained results are expected to expend the knowledge about the genetic variability of the snails and to permit the future identification of genomic sequences specifically related to the resistance/susceptibility of Biompholario to the larval forms of S. mansoni.
Keywords: biomphalaria; schistosomiasis; RAPD-PCR; genetic variability; polymorphism